A Fast, Efficient and Easy to Implement Method to Purify Bacterial Pili From Lacticaseibacillus rhamnosus GG Based on Multimodal Chromatography - Dos Santos Morais, Raphael; El-Kirat-Chatel, Sofiane; Burgain, Jennifer; Simard, Blandine; Barrau, Sarah; Paris, Cédric; Borges, Frédéric; Gaiani, Claire (Frontiers in Microbiology, 2020)
Pili are polymeric proteins located at the cell surface of bacteria. These filamentous proteins play a pivotal role in bacterial adhesion with the surrounding environment. They are found both in Gram-negative and Gram-positive bacteria but differ in their structural organization. Purifying these high molecular weight proteins is challenging and has certainly slowed down their characterization. Here, we propose a chromatography-based protocol, mainly relying on multimodal chromatography (core bead technology using Capto Core 700 resin), to purify sortase-dependent SpaCBA pili from the probiotic strain Lacticaseibacillus rhamnosus GG (LGG). Contrary to previously published methods, this purification protocol does not require specific antibodies nor complex laboratory equipment, including for the multimodal chromatography step, and provides high degree of protein purity. No other proteins were detectable by SDS-PAGE and the 260/280 nm ratio (~0.6) of the UV spectrum confirmed the absence of any other co-purified macromolecules. One can obtain ~50 µg of purified pili, starting from 1 L culture at OD600nm ≈ 1, in 2-3 working days. This simple protocol could be useful to numerous laboratories to purify pili from LGG easily. Therefore, the present work should boost specific studies dedicated to LGG SpaCBA pili and the characterization of the interactions occurring with their protein partners at the molecular level. Moreover, this straightforward purification process might be extended to the purification of sortase-dependant pili from other Gram-positive bacteria.